Artificial Intelligence, Robotics, Work and Productivity: The Role of Firm Heterogeneity - Fredrik Heyman; Pehr-Johan Norbäck; Lars Persson (Research Institute of Industrial Economics (IFN), 2021)
We propose a model with asymmetric firms where new technologies displace workers. We show that both leading (low-cost) firms and laggard (high-cost) firms increase productivity when automating but that only laggard firms hire more automation-susceptible workers. The reason for this asymmetry is that in laggard firms, the lower incentive to invest in new technologies implies a weaker displacement effect and thus that the output-expansion effect on labor demand dominates. Using novel firm-level automation workforce probabilities, which reveal the extent to which a firms' workforce can be replaced by new AI and robotic technology and a new shiftshare instrument to address endogeneity, we find strong empirical evidence for these predictions in Swedish matched employer-employee data.
Keywords: D2; J24; L2; O33; 330; AI&R Technology; Automation; Job displacement; Firm Heterogeneity; Matched employer-employee data